Temporal bias in case-control design: preventing reliable predictions of the future - William Yuan (Nature Portfolio, 2021)
One of the primary tools that researchers use to predict risk is the case-control study. Here, the authors identify a flaw, temporal bias, that is specific to and uniquely associated with these studies that occurs when the study period is not representative of the data that clinicians have during the diagnostic process, undermining the validity of predictions.